Use of ultrasound densitometry for the assess of structural and functional disorders of bone tissue and prediction of fractures risk - A. M. Ignatiev; N. I. Turchin; T. N. Yamilova (Kazimierz Wielki University, 2015)
Ignatiev A. M., Turchin N. I., Yamilova T. N. Use of ultrasound densitometry for the assess of structural and functional disorders of bone tissue and prediction of fractures risk. Journal of Education, Health and Sport. 2015;5(4):23-28. ISSN 2391-8306. DOI: 10.5281/zenodo.16590 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%284%29%3A23-28 https://pbn.nauka.gov.pl/works/553129 http://dx.doi.org/10.5281/zenodo.16590 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.01.2014. Revised 27.02.2015. Accepted: 15.03.2015.   USE OF ULTRASOUND DENSITOMETRY FOR THE ASSESS OF STRUCTURAL AND FUNCTIONAL DISORDERS OF BONE TISSUE AND PREDICTION OF FRACTURES RISK   A. M. IGNATIEV, N. I. TURCHIN, T. N. YAMILOVA   Odessa medical national university, Odessa     Abstract Objective: To determine the dependence of lumbar spine compression degree on BMD state and the patients' age. The relationship of BMD state, the patients' age and the degree of compression of the vertebrae were studied. Correlation and regression analysis of the relationship between SOS index, score of compression and patients' age have been examined. Results. The data obtained allowed us to develop a mathematical model for predicting BMD reduction and the severity of vertebral compression fractures. Conclusions. Ultrasonic indexes of  bone mineral density may be used not only for its screening assessment in general population of different ages, but also in assessing the degree of structural and functional changes of BT, predicting the severity of low-energy osteoporosis fractures. It will help to assign treatment in preclinical stage, and carry out prevention of compression fractures. Key words: bone mineral density, low-energy fracture, vertebra  compression.